PENGATURAN PENANAMAN MODAL ASING DI BIDANG JASA PERDAGANGAN EKSPOR - Alit Diputra, I Ketut; Ari Atu Dewi, A. A. Istri (Kertha Semaya : Journal Ilmu Hukum, 2013)
Management of Foreign Capital Investment establishment in export trading service in Indonesia is referred to Republic Indonesia Act Number 25 of 2007 concerning Foreign Capital Investment in Chapter IV Legal Formation, Position and Area Business, as listed in Article 5 point 2 mentioned that: the company intended in Article 1 which runs its business wholly or mostly in Indonesia as a unit of company must be in the form of legal body of Indonesian law and has its registered office in Indonesia. The legal body existing in Indonesia as listed in Article 1 of RI Act Number 40 of 2007 concerning Limited Partnership is defined as legal body established based on agreement that conduct business activity where its all basic capital divided into dividend and fulfills requirement as determined in this Act as well as implementation regulation.The policies of legal instruments done by BKPMD/BPM in increasing foreign capital investment climate in the field of export trade, the policies taken by BPM Bali Province for the sake of attracting investors for their investment in Bali in general, so BKPMD Bali Province still refers to Deputy Letter of National Entrepreneurship Development, BPM Number S-35/DU-5BKPM/2001 such as: in promotion and international cooperation of capital investment, covering: promotion implementation of local capital investment both domestic and foreign ones, material availability of local capital investment in term of printing media, collaboration between provincial and center government in implementing local capital investment, partnership implementation, cooperation with third parties as the step promotion to abroad, mission delivery to abroad, acceptance of capital investment mission from other areas and abroad, collaboration with foreign countries as long as no violation to center government, agreement preparation for the sake of sub regional cooperation, socialization to government staff and business body in term of capital investment, other authorities as long as no violation with policy of center and local governments. The field of license service of capital investment covers: agreement given to all projects and expansion of PMDN under responsibility of provincial and center governments, agreement given to PMDN project amendment, license issuance, vacancy license given for foreigners who work in a city or regency, incentive given limited to authority, implementation of other authority, in addition there is another step taken by BPMD of Bali Province in increasing investment is through creation of healthy investment competition, especially in trading conducted by tariff deduction and less administration as well as conducting illumination.
Keywords: Foreign Capital Investment, Export Trade Service